An infection-age-structured modelling for Monkey-Pox disease dynamics incorporating control measures - Lasisi *†, N. O.; Ejiwole ‡, O.J.; Azuaba†§, E.; Ibrahim†** , A. A. (International Journal of Mathematical Analysis and Modelling, 2024)
Monkey-pox is known as pathogens affecting livestock animals and humans and belongs to the orthopox virus. The pathogen causes lymph nodes to swell and increasing transmission risk associated with factors involving introduction of virus to the oral mucosa. In this paper, we developed an Age-Structured model for Monkey-pox disease in a population with vital dynamics, incorporating standard incidence rate and vaccination. We showed the existence and uniqueness of the solution of the model. We obtained the Disease-Free Equilibrium state and shown the effective reproduction number of the model. We proved the conditions for Local and Global Stability of the Disease-Free Equilibrium (DFE) State and we found that the disease free equilibrium state is locally asymptotically stable if 1 )0( G (RE < 1) and Globally Asymptotically Stable (GAS) in Ω if RE ≤ 1 while unstable if RE ≥ 1.